African languages in teaching and learning : Implementing and promoting multilingualism and decolonisation in South African higher education - Ntombela, Berrington; Canagarajah, Suresh; Ngubane, Nomalungelo (African Perspectives of Research in Teaching and Learning Journal (APORTAL), 2024)
Refer to the document
Journal article published in African Perspectives of Research in Teaching and Learning Journal Issue 3, Volume 8, 2024 Special Issue
Keywords: African languages; Teaching and learning; Multilingualism; Decolonisation; South African higher education; African languages; Active learning; Multilingual education; Education, Higher -- South Africa; Language and languages